Proposal for the Design of an Articulable Robot for Taking Low-Cost Measurements in the Preoperative Phase of Maxillofacial Surgery - Arhuis Quintana, Anthoni Jesús (2024)
This research paper presents the design of an articulable robot for low-cost measurement in people needing maxillofacial surgery. It is observed that it is possible to improve the measurement accuracy, significantly reduce the error rate and risk to the patient, while reducing the manufacturing cost. This design presents a stable structure for the maxillofacial surgeon, an intuitive interface for the user, in addition to stepper motor actuators that allow the movement of the axes, worm screws and rack and pinion, where there is greater precision and speed, as well as a Raspberry Pi Pico W microprocessor that controls the articulating robot with great efficiency and with sufficient memory to store and carry out the purpose for which it was designed. In order to consolidate the objectives, set at the beginning, the mixed methodology between VDI 2206 and MIT was developed and used. The results obtained will not only serve to create articulable and controllable robots with low complexity costs, but also to reduce the error rate and reduce the risk for the patient, promoting the use of robotics in medicine and involving the new proposed methodology to research projects.